148k views
0 votes
Rationalize the denominator and simplify. StartFraction 5 minus StartRoot 3 EndRoot Over 4 plus 2 StartRoot 3 EndRoot EndFraction

User Prattski
by
5.7k points

2 Answers

3 votes

Answer:

0.25

Explanation:

User GoPro
by
5.9k points
3 votes

Answer:


(13-7√(3))/(2)

Explanation:

We need to rationalize the denominator of
= (5-√(3))/(4+2√(3)). For rationalizing we multiply the equation by
(4-2√(3))/(4-2√(3))

So, solving


= (5-√(3))/(4+2√(3))*(4-2√(3))/(4-2√(3)) \\=((5-√(3))(4-2√(3)))/(4+2√(3)*4-2√(3))\\=((5-√(3))(4-2√(3)))/((4)^2-(2√(3))^2)\\= (5(4-2√(3))-√(3)(4-2√(3)))/(16-(4*3))\\=(20-10√(3)-4√(3)+2*3)/(16-12)\\=(20+6-14√(3))/(4)\\=(26-14√(3))/(4)\\= (2(13-7√(3)))/(4)\\=(13-7√(3))/(2)